Measuring The Level of Cybersecurity Awareness of Social Media Users Among Students - Muhammad Agung Al Affan; Mona Fronita; Eki Saputra; Muhammad Luthfi Hamzah; Zarnelly (P3M Politeknik Negeri Bengkalis, 2025)
The role of social media is increasingly important and easily accessible through mobile phones, slowly replacing conventional mass media. The development of Internet technology has made many users forget the importance of cybersecurity awareness, which impacts social media activities. As a result, cyber-attacks on social networks are now more frequent because many users still need help understanding cybersecurity well. Based on data BSSN, cyberattacks in Indonesia increased significantly from 290.3 million in 2019 to 495.3 million in 2020, representing a 41% rise. Social media users need to understand cybersecurity, a technology that protects data, networks, and programs from illegal access or digital attacks, known as cybercrime. Eighty-four respondents participated in the study. This study aims to measure the level of cybersecurity awareness and contribute to the existing literature by providing empirical insights into the level of cybersecurity awareness among university students. This study can also help raise awareness among the public, particularly young users, about the importance of protecting privacy and security while engaging in the digital world. This behaviour is measured using the five TPB variables: attitude, subjective form, perceived behaviour control, intention, and behaviour. Variables from TPB are then processed using SEM-PLS tools with the help of SmartPLS. Based on the study's results, it is concluded that the attitude and subjective form variables do not significantly affect the intention variable. In contrast, the perceived behaviour control variable significantly affects the intention variable, and the behaviour variable significantly affects intention.